Animal Spirits, Heterogeneous Expectations and the Emergence of Booms and Busts - Tiziana Assenza; William A. Brock; Cars H. Hommes (Tinbergen Institute, 2013)
We introduce a simple equilibrium model of a market for loans, where households lend to firms based on heterogeneous expectations about their loan default probability. Agents select among heterogeneous expectation rules, based upon their relative performance. A small fraction of pessimistic traders already has a large aggregate effect, leading to a crisis characterized by high contract rates for loans and low output. Our stylized model illustrates how animal spirits and heterogeneous expectations amplify boom and bust cycles and how endogenous coordination on pessimistic expectations amplifies crises and slows down recovery. Taking heterogeneous expectations and bounded rationality into account is crucial for the timing of monetary or fiscal policy.
Keywords: E32; D83; D84; 330; Heterogeneous Expectations; Crises; Animal Spirits